Comprehensive bio-imaging using myocardial perfusion reserve index during cardiac magnetic resonance imaging and high-sensitive troponin T for the prediction of outcomes in heart transplant recipients - Hofmann, Nina; Steuer, Christian; Voß, Andreas; Erbel, Christian; Celik, Sultan; Dösch, Andreas; Ehlermann, Philipp; Giannitsis, Evangelos; Buß, Sebastian Johannes; Katus, Hugo; Korosoglou, Grigorios (American journal of transplantation, 2014)
We sought to determine the ability of quantitative myocardial perfusion reserve index (MPRI) by cardiac magnetic resonance (CMR) and high-sensitive troponin T (hsTnT) for the prediction of cardiac allograft vasculopathy (CAV) and cardiac outcomes in heart transplant (HT) recipients. In 108 consecutive HT recipients (organ age 4.1 ± 4.7 years, 25 [23%] with diabetes mellitus) who underwent cardiac catheterization, CAV grade by International Society for Heart & Lung Transplantation (ISHLT) criteria, MPRI, late gadolinium enhancement (LGE) and hsTnT values were obtained. Outcome data including cardiac death and urgent revascularization (“hard cardiac events”) and revascularization procedures were prospectively collected. During a follow-up duration of 4.2 ± 1.4 years, seven patients experienced hard cardiac events and 11 patients underwent elective revascularization procedures. By multivariable analysis, hsTnT and MPRI both independently predicted cardiac events, surpassing the value of LGE and CAV by ISHLT criteria. Furthermore, hsTnT and MPRI provided complementary value. Thus, patients with high hsTnT and low MPRI showed the highest rates of cardiac events (annual event rate = 14.5%), while those with low hsTnT and high MPRI exhibited excellent outcomes (annual event rate = 0%). In conclusion, comprehensive “bio-imaging” using hsTnT, as a marker of myocardial microinjury, and CMR, as a marker of microvascular integrity and myocardial damage by LGE, may aid personalized risk-stratification in HT recipients.
Gesehen am 16.10.2020